Prediction and Evaluation of Athletes’ Positive Emotions Based on Emotional Intelligence Theory - Huayu Zhao (Revista de Psicología del Deporte (Journal of Sport Psychology), 2021)
Emotional intelligence is the ability to evaluate, express, and control emotions experienced by oneself and others. Emotional intelligence explains and predicts individual achievement, and the complementarity of traditional and emotional intelligence is the key to individual success. The theory of emotional intelligence leads to re-examine the concept and essence of an athlete's intelligence, and raises new questions about the measurement of intelligence and emotion in athletes. In this study, the theoretical model of team emotional intelligence is developed based on emotional psychology, symbolic interaction theory and information processing theory. This theoretical framework is combined with the specific situation of the game, using literature review, interview method, questionnaire method as well as mathematical and tatistical methods that employ a "Team Emotional Intelligence Scale". The researcher seeks to conduct a comparative study on team emotional intelligence of different athletes, coaches and different level teams. The results show that teams with athletes' average age in the range of 20-21 years performs better in team emotional cognitive ability, and poorer in terms of team emotional intelligence and team emotional sharing, evaluation and normative ability. The higher the percentage of athletes' sports rank, the higher the team emotional intelligence; the longer the team's formation years, the stronger the team emotional cognitive ability. The better the team’s competition performance, the stronger the team’s emotional intelligence and team emotional sharing, evaluation and normative ability, but the weaker the team emotional cognitive ability; the female coaches' team emotional cognitive ability is found to be better than the male coaches' team emotional cognitive ability.